Bird communities in the tropical peri-urban landscape of Bogor, Indonesia - SEPTIAN PUTRA ADI NUGROHO; ANI MARDIASTUTI; YENI ARYATI MULYANI; DEDE AULIA RAHMAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nugroho SPA, Mardiastuti A, Mulyani YA, Rahman DA. 2023. Bird communities in the tropical peri-urban landscape of Bogor, Indonesia. Biodiversitas 24: 6988-7000. Amidst the urbanization threat, peri-urban landscapes can play an important role in biodiversity conservation, particularly among birds. Therefore, to study species and functional diversity of bird communities in the tropical peri-urban landscape, we observed four habitat types (forest, plantation, built-up area, and farmland) in the Ciampea-Dramaga Landscape, Bogor, Indonesia, from September to December 2020 and September to December 2021. A standard point method was used to observe birds, and several diversity indices were used for data analysis. Altogether, we recorded 11,290 individual birds of 61 species and 33 families. The species diversity tended to be higher in the increasing habitat succession stages. Forest had the highest species diversity (H?=3.17), followed by plantation (H?=2.87), built-up area (H?=2.54), and farmland (H?=2.23). Meanwhile, functional diversity revealed that all feeding guilds can be observed in the forest. The species richness of frugivore-insectivores dominated all habitats, and their abundance are also dominated in forest and plantation habitats. In contrast, granivores dominated farmland, and fly-catching insectivores dominated built-up areas. Due to its relatively high bird diversity in the study area, it needed to be conserved, including habitat management at the landscape scale, strengthening policies and conservation actions, and raising public awareness.